2021
DOI: 10.1186/s13075-021-02701-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between female reproductive factors and gout: a nationwide population-based cohort study of 1 million postmenopausal women

Abstract: Background Previous studies have shown that the incidence and risk factors of gout differs according to sex. However, little research has been done on the association between reproductive factors and gout. We conducted an analysis of a large nationwide population-based cohort of postmenopausal women to determine whether there is an association between reproductive factors and the incidence of gout. Methods A total of 1,076,378 postmenopausal women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Indeed, females are generally more concerned about body appearance [ 26 28 ], but older age was independently associated with higher attitude scores, as supported by an Australian study [ 26 ]. In addition, before menopause, women are protected by estrogens against the development of hyperuricemia and other metabolic disorders [ 29 31 ], possibly making younger women adopt a more casual attitude toward hyperuricemia. As individuals age, they can become more concerned with their health.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, females are generally more concerned about body appearance [ 26 28 ], but older age was independently associated with higher attitude scores, as supported by an Australian study [ 26 ]. In addition, before menopause, women are protected by estrogens against the development of hyperuricemia and other metabolic disorders [ 29 31 ], possibly making younger women adopt a more casual attitude toward hyperuricemia. As individuals age, they can become more concerned with their health.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fact that the median age at menopause among women from industrialized countries ranges between 50 and 52 years [40], one can assume that the menopause status may explains the exclusive significant association of gout and BC in women aged < 50. Indeed, it is known that postmenopausal women experience a higher occurrence of gout, while estrogen's uricosuric effect shields premenopausal women [41]. Given the positive association between hyperuricemia and higher cancer incidence (incl.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the morbidity of CVDs is lower in premenopausal women than in men but increases in postmenopausal women, as much as in men, because of the loss of the hormonal protective effects of endothelial dysfunction, which hinders atherosclerosis and CVD 36 . In addition, because estradiol lowers serum uric acid levels by renal clearance, secretion, and reabsorption, postmenopausal women with low ovarian hormone levels have high uric acid levels 37 . A study reported that estradiol changes according to sleep patterns.…”
Section: Discussionmentioning
confidence: 99%
“… 36 In addition, because estradiol lowers serum uric acid levels by renal clearance, secretion, and reabsorption, postmenopausal women with low ovarian hormone levels have high uric acid levels. 37 A study reported that estradiol changes according to sleep patterns. Michels et al 38 found a decrease in average estradiol in women with sleep less than 7 hours per day.…”
Section: Discussionmentioning
confidence: 99%